2007
DOI: 10.1128/jb.01126-06
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of lptA and lptB , Two Essential Genes Implicated in Lipopolysaccharide Transport to the Outer Membrane of Escherichia coli

Abstract: The outer membrane (OM) of gram-negative bacteria is an asymmetric lipid bilayer that protects the cell from toxic molecules. Lipopolysaccharide (LPS) is an essential component of the OM in most gram-negative bacteria, and its structure and biosynthesis are well known. Nevertheless, the mechanisms of transport and assembly of this molecule in the OM are poorly understood. To date, the only proteins implicated in LPS transport are MsbA, responsible for LPS flipping across the inner membrane, and the Imp/RlpB co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
246
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 219 publications
(262 citation statements)
references
References 43 publications
15
246
0
1
Order By: Relevance
“…Light microscopy also showed that all three depletion strains form filaments composed of 10-20 cells with constricted septa when grown without arabinose (data not shown). In agreement with our hypothesis that LptF and LptG are involved in LPS transport, similar phenotypes have been reported for cells where each of the lpt gene products LptABDE have been depleted (17)(18)(19).…”
Section: Identification Of Lptfg Assupporting
confidence: 77%
See 4 more Smart Citations
“…Light microscopy also showed that all three depletion strains form filaments composed of 10-20 cells with constricted septa when grown without arabinose (data not shown). In agreement with our hypothesis that LptF and LptG are involved in LPS transport, similar phenotypes have been reported for cells where each of the lpt gene products LptABDE have been depleted (17)(18)(19).…”
Section: Identification Of Lptfg Assupporting
confidence: 77%
“…S2) revealed that in the presence of inducer, the cell envelope of the LptFG double-depletion strain appears normal, but depletion of LptFG results in defective envelopes that include extra membranous material in the periplasm. This phenotype is characteristic of cells where LPS transport has been compromised (18,19).…”
Section: Low Levels Of Lptf And/or Lptg Cause Increased Om Permeabilimentioning
confidence: 99%
See 3 more Smart Citations